Artificial cells with liquid–liquid phase separation–regulated cell-free protein synthesis - Dongdong Fan; Kaini Liang; Bingjie Wu; Michael W. Chen; Chengyu Sun; Lei Sun; Yan Zhang; Yanan Du (Proceedings of the National Academy of Sciences, 2025)
The rapid advancement of synthetic biology has enabled the construction of artificial cells that closely mimic the morphology and functionality of their natural counterparts. However, significant limitations remain in engineering artificial cells capable of regulated protein expression. Here, we demonstrate that engineered polymers containing multivalent association motifs can reversibly regulate translational activity through liquid–liquid phase separation (LLPS)–induced protein aggregation, enabling precise temporal control of cell-free protein synthesis (CFPS) activity. This aggregation mechanism exerts a broad inhibitory effect on various enzymes and facilitates the construction of artificial cells with controllable reaction processes. Leveraging this phenomenon, we have developed a microfluidic platform to fabricate giant unilamellar vesicles (GUVs) that encapsulate CFPS systems, thereby constructing artificial cells with finely tunable protein expression. By incorporating targeted DNA templates, these artificial cells can selectively express specific proteins in response to pH adjustments. Furthermore, in vivo studies using a bile duct ligation mouse model with liver injury further confirmed significant differences in protein expression under alkaline conditions compared to neutral conditions. Our findings highlight the potential of leveraging aggregate dynamics for precise, in situ modulation of protein synthesis within artificial cells, thereby opening avenues for their advanced biomedical applications.